Super-hard (MoSiTiVZr)Nx high-entropy nitride coatings - Li, Jingchuan; Chen, Yujie; Zhao, Yiman; Shi, Xunwang; wang, Shu; Zhang, Sam (Journal of alloys and compounds, 2022)
High-entropy nitride coatings have become a promising alternative to traditional protective coatings due to their excellent mechanical properties, thermal stability, oxidation, and wear resistance. However, the design and fabrication of hard high-entropy nitride coatings remain a great challenge. In this study, (MoSiTiVZr)Nx high-entropy nitride coatings were deposited by reactive DC magnetron sputtering at different nitrogen flow. The chemical compositions, structures, hardness, damage-tolerance, friction and corrosion resistances of the coatings were investigated. With the increase of nitrogen content in the coatings, the phase structure transforms from an amorphous structure to a single face centered cubic structure, and all alloying elements form metal-nitrogen bonds. The coating with nitrogen content of 53.7 at% exhibits an ultrahigh hardness of 45.6 GPa and the best damage-tolerance and wear resistance. The coatings with low nitrogen contents show better corrosion resistance than 304 stainless steels, however, an increase in nitrogen content results in a slight decrease in corrosion resistance. The mechanism of the structures, mechanical properties and corrosion resistance of (MoSiTiVZr)Nx coatings are discussed in details. •(MoSiTiVZr)Nx coatings were deposited by reactive magnetron sputtering.•Effect of N addition on structures and properties of the coatings was studied.•The structure of the coatings changes from an amorphous to a single FCC structure.•The maximum hardness of the coating reaches super hard level of 45.6 GPa.